1996
DOI: 10.1046/j.1365-2362.1996.120270.x
|View full text |Cite
|
Sign up to set email alerts
|

Complete congenital heart block is associated with increased autoantibody titers against calreticulin

Abstract: Abstract. Complete congenital heart block (CCHB) is associated with anti-Ro/SS-A and anti-La/SS-B antibodies. Calreticulin, a calcium-binding, multifunctional protein of the endoplasmic reticulum with C-terminal KDEL-sequence, is not part of the Ro/SS-A ribonucleoprotein complex. In this study anti-calreticulin autoantibody responses in serum samples from 18 infants with CCHB, their mothers and in a control group of 11 antiRo/SS-A or anti-La/SS-B positive infants without heart block and their mothers were anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
2

Year Published

1999
1999
2012
2012

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(23 citation statements)
references
References 27 publications
1
20
0
2
Order By: Relevance
“…A previous study has suggested that complete heart block may be associated with production of an autoantibody against calreticulin (16,17). Therefore, we investigated the possibility that overexpression of calreticulin in the transgenic mice might lead to secretion of the protein and/or production of anti-calreticulin antibod-…”
Section: Resultsmentioning
confidence: 99%
“…A previous study has suggested that complete heart block may be associated with production of an autoantibody against calreticulin (16,17). Therefore, we investigated the possibility that overexpression of calreticulin in the transgenic mice might lead to secretion of the protein and/or production of anti-calreticulin antibod-…”
Section: Resultsmentioning
confidence: 99%
“…The autoantibody-mediated immune response to calreticulin isoforms was found in pancreatic [24] and gastric cancer [25]. Increased levels of IgA and/or IgG anti-calreticulin antibodies in the sera of many patients with HCC and colorectal adenocarcinoma and 47% of patients with pancreatic adenocarcinoma (PACA) were found.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] In the ER, CRT has a number of functions, including Ca 2+ sensing, protein folding and a role in MHC class I assembly. 4 The multifunctional nature of CRT suggests that it may be prevalent in many cellular compartments.…”
Section: Introductionmentioning
confidence: 99%